Glass filter material and preparation method thereof

By spraying the nanodispersion and drying and sintering, the surface structure of the glass filter material is improved, the problem of insufficient filtration accuracy and service life of traditional filter materials is solved, and the effect of efficient filtration, antibacterial and oleophobic effects is achieved. At the same time, the process is simple and the cost is low.

CN119551911AActive Publication Date: 2025-03-04TIANJIN ZHIQING FUTURE TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510043688.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-04
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

Traditional water-quality filter materials such as quartz sand, anthracite and activated carbon have shortcomings in filtration accuracy and service life, especially when glass filter materials are used directly, the filter accuracy is low, and it needs to be improved through "capacity expansion" and anti-fouling treatment.

Method used

By spraying the nanodispersion liquid on the surface of the glass particles and drying and sintering, a rough surface of the complex structure is formed, which improves the specific surface area and antibacterial properties of the glass filter material.

Benefits of technology

The high filtration accuracy, antibacterial and oleophobic effects of glass filter materials are achieved, while simplifying the production process and reducing manufacturing costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005237690450000071
    Figure BDA0005237690450000071
  • Figure BDA0005237690450000081
    Figure BDA0005237690450000081
Patent Text Reader

Abstract

The invention discloses a glass filter material and a preparation method thereof, and belongs to the technical field of water treatment. The preparation method comprises the following steps: spraying the nano dispersion liquid on the surfaces of the glass particles, and then drying and sintering to obtain the glass. The product prepared by the preparation method is screened into four grades, namely 0.1 mm to 0.4 mm, 0.4 mm to 0.8 mm, 0.8 mm to 2.0 mm and 2.0 mm to 4.0 mm, so as to adapt to different filtering accuracies. By introducing the nano dispersion liquid, the glass particles are endowed with larger specific surface area in an addition form, and meanwhile, the glass particles have the characteristics of high filtering precision, antibacterial property, oleophobic property and the like, and the production process is simple and the manufacturing cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a glass filter material and a preparation method thereof. Background Art

[0002] Filtration is a widely used process in water treatment. The filter layer material can intercept suspended impurities in water, reduce COD and BOD, heavy metal ion concentration, oil content and color and other indicators. Traditional water quality filter materials generally use quartz sand, anthracite, ceramsite and other materials, but there are problems such as low filtration accuracy and short service life, and frequent backwashing operations are required. Activated carbon filter materials can improve filtration accuracy, but their micro-nano pore structure is easily blocked by small molecular organic matter, which reduces the filtration efficiency.

[0003] Glass is acid-resistant, alkali-resistant, and recyclable, and is a potential high-quality filter material. However, using glass particles directly as filter material still has the problem of low filtration accuracy. It is necessary to take appropriate methods to "expand" and anti-fouling treatment, that is, to increase the specific surface area of ​​glass particles, make the glass surface carry negative charges and antibacterial and antibacterial materials, so as to achieve high filtration accuracy and long service life.

[0004] Patent CN111097230B discloses boiling the screened glass filter material in distilled water for 30 minutes, repeatedly rinsing with distilled water, drying and cooling at a high temperature of 110°C, and then soaking in a 1 mol / L hydrogen chloride HCL solution for 24-36 hours after cooling. It requires a long acid treatment process, a long process, and the waste acid solution needs to be disposed of during the specific implementation process.

[0005] Patent CN110548339A discloses that the glass slag raw material after being dried by nitrogen is placed in 100 ml of "anthropic acid" solution (the volume ratio of concentrated sulfuric acid and hydrogen peroxide is 7:3), and then placed in a water bath at 95°C for 2 hours. It is still necessary to dispose of the waste acid solution.

[0006] Patent CN113735462B discloses placing waste glass particles in a piranha solution, subjecting the surface to a hydroxylation treatment at 90°C for 30 minutes, washing with water until the washing solution is neutral, and then drying at 100°C for 2 hours to obtain hydroxylated waste glass. During the implementation of this patent, the waste acid solution also needs to be disposed of. Summary of the invention

[0007] The purpose of the present invention is to provide a glass filter material and a preparation method thereof, which can give glass particles a larger specific surface area by introducing a nano-dispersion in the form of "addition", and at the same time make it have the characteristics of high filtering accuracy, antibacterial, oleophobic, etc., and the production process is simple and the manufacturing cost is low.

[0008] To achieve the above objectives, the present invention adopts the following specific technical solutions:

[0009] The invention provides a method for preparing a glass filter material: the nanometer dispersion liquid is sprayed on the surface of glass particles, and then dried and sintered to obtain the glass filter material.

[0010] Furthermore, the glass particles have a particle size of 0.1-4.0 mm.

[0011] Furthermore, the glass particles are subjected to surface cleaning treatment.

[0012] Optionally, the surface cleaning process includes plasma cleaning or ultraviolet irradiation; further, the plasma cleaning time is 1-10 seconds.

[0013] Furthermore, the preparation method of the nano-dispersion liquid includes: configuring fumed silica, aluminum oxide, zinc oxide, titanium oxide and water into an aqueous solution according to weight parts, grinding to ensure that the nano-powder is fully dispersed, deagglomerated and broken up the agglomerated particles, and then adding silica sol and water, stirring to obtain a nano-dispersion liquid with a silica sol concentration of 5-35%, containing powder particles with a size ranging from a few nanometers to more than one micron.

[0014] Preferably, the D50 of the fumed silica is 20-100 nm and the BET specific surface area is 115-135 m 2 / g.

[0015] Preferably, the particle size of the alumina is 100-2000 nm and the BET specific surface area is 5-10 m 2 / g. By adding alumina particles of several hundred to thousands of nanometers, and grading particles of different sizes such as silica sol and fumed silica, a surface morphology with rich structure is finally formed, which greatly improves the material's pollution holding capacity and obtains high-precision filter materials.

[0016] Preferably, the particle size of the zinc oxide is less than 100 nm. Zinc oxide is a common antibacterial material that destroys the structure and metabolism of bacteria through various mechanisms such as photocatalysis, ion dissolution and electron transfer, thereby achieving the effect of inhibiting bacterial growth and reproduction.

[0017] Preferably, the titanium oxide includes two crystal structures of rutile and anatase, and its particle size is less than 50nm. P25 (titanium dioxide of mixed phase of anatase crystal and rutile crystal with an average particle size of 25nm) is preferably used. When anatase titanium dioxide is irradiated with light with energy greater than its energy band, electrons and holes will be generated, and they will react with water and oxygen to produce active components such as active hydroxyl radicals and peroxides. These active components have strong reactivity, especially active hydroxyl radicals, which have an energy of 120kal / mol. The covalent bonds of carbon-carbon, carbon-nitrogen, carbon-hydrogen, oxygen-hydrogen, and nitrogen-hydrogen that constitute organic compounds have a binding energy of about 100kal / mol, that is, these active hydroxyl radicals can decompose organic compounds.

[0018] Furthermore, in parts by weight, the fumed silica, aluminum oxide, zinc oxide, titanium oxide and water are 1-50 parts, 1-10 parts, 0.1-20 parts, 0.1-20 parts and 100-800 parts respectively.

[0019] Furthermore, the ratio of the glass particles to the nano-dispersion liquid is 8-12 g / ml.

[0020] Furthermore, the drying temperature is 80-250° C., and the drying time is 5-60 min.

[0021] Furthermore, the sintering temperature is 500-700°C and the sintering time is 5-30 minutes, so that the surface of the glass particles is softened, and the nanoparticles and the glass are bonded together to form a coating with a strong structure. The coating contains particles of several nanometers to tens of nanometers, which can make the glass particles have negative charges in the aqueous solution. The negative charge has the same electrical properties as the particles in the water body to be filtered and purified, and repel each other, so it will not be adsorbed on the surface of the glass particles.

[0022] The invention also provides a glass filter material. The product prepared by the preparation method is screened into four grades, namely 0.1-0.4 mm, 0.4-0.8 mm, 0.8-2.0 mm and 2.0-4.0 mm, so as to adapt to different filtering precisions.

[0023] Compared with the prior art, the present invention uses a dispersion containing nano-scale silicon oxide, zinc oxide, titanium oxide, aluminum oxide, and silica sol, sprays it on the surface of glass particles, and then performs drying and sintering treatments to form a rough surface with a complex structure on the surface of the glass particles; in particular, nanoparticles of different sizes and functions eventually form a rough surface structure on the surface of the glass particles, and the structure has a size span of several nanometers to more than one micron in the "horizontal direction" and a size span of several nanometers to more than one micron in the "vertical direction". Finally, a glass particle filter material with high filtration accuracy, antibacterial and oleophobic properties is obtained, and the present invention has the characteristics of simple process and low production cost. DETAILED DESCRIPTION

[0024] The embodiments of the present invention will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If specific conditions are not specified in the examples, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0025] In the following examples or comparative examples, the aluminum oxide was ALMATIS CT3000 (D50 = 0.4 μm, D90 = 1.3 μm, Bet 7.5 μm 2 / g); fumed silica uses Cabot TS-610 (D50 = 50nm, Bet specific surface area is 120 ± 15m 2 / g); zinc oxide uses Aladdin Z141332 (0-100nm); titanium oxide uses Degussa's Evonik P25.

[0026] In the following embodiments or comparative examples, filtration accuracy refers to: using 0.1-0.4 mm glass particle filter material to filter sewage, the water sample obtained is tested using a laser particle size analyzer, D97: refers to the particle size value corresponding to the cumulative distribution percentage from small to large in the particle size distribution reaching 97%, and the number of particles with a particle size smaller than D97 accounts for 97% of the total number of particles.

[0027] The shading rate refers to: the treated water sample is tested using a laser particle size analyzer, and the amount of water sample added each time is consistent. The smaller the shading rate value, the higher the clarity and transparency of the water sample, that is, the better the filtering effect.

[0028] Example 1

[0029] A method for preparing a glass filter material:

[0030] (1) 3 g of fumed silica, 3 g of alumina, 0.2 g of zinc oxide, 0.1 g of P25 and 6.3 ml of water were prepared into a 50% aqueous solution and ground for 4 hours to fully disperse the nanopowder and reduce agglomeration; then 75 g of commercially available weakly acidic 40% silica sol was added and stirred to mix evenly, and then 12.4 ml of pure water was added and stirred for 30 minutes to obtain a nano-dispersion liquid with a silica sol concentration of 30%.

[0031] (2) Clean glass particles with a particle size of 0.1-4.0 mm are used as raw materials and plasma cleaning is performed for 3 seconds to clean the surface.

[0032] (3) Take 1000g of glass particles, spray 100ml of the above nano-dispersion liquid while stirring, then dry at 120℃ for 30min, sinter at 600℃ for 25min, and obtain the glass filter material after cooling. The obtained glass filter material is sieved into four grades, namely 0.1-0.4mm, 0.4-0.8mm, 0.8-2.0mm and 2.0-4.0mm, to adapt to different filtering precisions. Among them, the filtration precision of the glass filter material of 0.1-0.4mm grade is 0.95 microns; the filtration precision of the glass filter material of 0.4-0.8mm grade is about 3.0 microns. The specific filtering effect is shown in Table 1.

[0033] Example 2

[0034] A method for preparing a glass filter material:

[0035] (1) 2 g of fumed silica, 2 g of alumina, 0.1 g of zinc oxide, 0.1 g of P25 and 4.2 ml of water were prepared into a 50% aqueous solution and ground for 4 hours to fully disperse the nanopowder and reduce agglomeration; then 87.5 g of commercially available weakly acidic 40% silica sol was added and stirred to mix evenly, and then 4.1 ml of pure water was added and stirred for 30 minutes to obtain a nano-dispersion liquid with a silica sol concentration of 35%.

[0036] (2) Clean glass particles with a particle size of 0.1-4.0 mm are used as raw materials and plasma cleaning is performed for 3 seconds to clean the surface.

[0037] (3) 1000 g of glass particles were taken, 100 ml of the above nano-dispersion liquid was sprayed on them while stirring, and then dried at 120° C. for 30 min, and then sintered at 600° C. for 25 min. After cooling, the glass filter material was obtained.

[0038] The obtained glass filter material is sieved into four grades, namely 0.1-0.4mm, 0.4-0.8mm, 0.8-2.0mm and 2.0-4.0mm, to adapt to different filtering precisions. Among them, the 0.1-0.4mm grade glass filter material has a filtering precision of 1.7 microns. The specific filtering effect is shown in Table 1.

[0039] Example 3

[0040] A method for preparing a glass filter material:

[0041] (1) 4 g of fumed silica, 3 g of aluminum oxide, 0.1 g of zinc oxide, 0.1 g of P25 and 7.2 ml of water were prepared into a 50% aqueous solution and ground for 4 hours to fully disperse the nanopowder and reduce agglomeration; then 50 g of commercially available weakly acidic 40% silica sol was added and stirred to mix evenly, and then 35.6 ml of pure water was added and stirred for 30 minutes to obtain a nano-dispersion liquid with a silica sol concentration of 20%.

[0042] (2) Clean glass particles with a particle size of 0.1-4.0 mm are used as raw materials and plasma cleaning is performed for 3 seconds to clean the surface.

[0043] (3) 1000 g of glass particles were taken, 100 ml of the above nano-dispersion liquid was sprayed on them while stirring, and then dried at 120° C. for 30 min, and then sintered at 600° C. for 25 min. After cooling, the glass filter material was obtained.

[0044] The obtained glass filter material is sieved into four grades, namely 0.1-0.4mm, 0.4-0.8mm, 0.8-2.0mm and 2.0-4.0mm, to adapt to different filtering precisions. Among them, the 0.1-0.4mm grade glass filter material has a filtering precision of 5.3 microns. The specific filtering effect is shown in Table 1.

[0045] Example 4

[0046] A method for preparing a glass filter material:

[0047] (1) 3 g of fumed silica, 3 g of alumina, 0.2 g of zinc oxide, 0.1 g of P25 and 6.3 ml of water were prepared into a 50% aqueous solution and ground for 4 hours to fully disperse the nanopowder and reduce agglomeration; then 75 g of commercially available weakly acidic 40% silica sol was added and stirred to mix evenly, and then 12.4 ml of pure water was added and stirred for 30 minutes to obtain a nano-dispersion liquid with a silica sol concentration of 30%.

[0048] (2) Clean glass particles with a particle size of 0.1-4.0 mm are used as raw materials and plasma cleaning is performed for 5 seconds to clean the surface.

[0049] (3) Take 800 g of glass particles, spray 100 ml of the above nano-dispersion liquid while stirring, then dry at 100° C. for 60 min, and then sinter at 650° C. for 20 min. After cooling, the glass filter material is obtained.

[0050] The obtained glass filter material is sieved into four grades, namely 0.1-0.4mm, 0.4-0.8mm, 0.8-2.0mm and 2.0-4.0mm, to adapt to different filtering accuracies. Among them, the 0.1-0.4mm grade glass filter material has a filtering accuracy of 0.94 microns. The specific filtering effect is shown in Table 1.

[0051] Example 5

[0052] A method for preparing a glass filter material:

[0053] (1) 3 g of fumed silica, 3 g of alumina, 0.2 g of zinc oxide, 0.1 g of P25 and 6.3 ml of water were prepared into a 50% aqueous solution and ground for 4 hours to fully disperse the nanopowder and reduce agglomeration; then 75 g of commercially available weakly acidic 40% silica sol was added and stirred to mix evenly, and then 12.4 ml of pure water was added and stirred for 30 minutes to obtain a nano-dispersion liquid with a silica sol concentration of 30%.

[0054] (2) Clean glass particles with a particle size of 0.1-4.0 mm are used as raw materials and plasma cleaning is performed for 3 seconds to clean the surface.

[0055] (3) 1200 g of glass particles were taken, 100 ml of the above nano-dispersion liquid was sprayed on them while stirring, and then dried at 220° C. for 5 min, and then sintered at 550° C. for 30 min. After cooling, the glass filter material was obtained.

[0056] The obtained glass filter material is sieved into four grades, namely 0.1-0.4mm, 0.4-0.8mm, 0.8-2.0mm and 2.0-4.0mm, to adapt to different filtering precisions. Among them, the 0.1-0.4mm grade glass filter material has a filtering precision of 1.12 microns. The specific filtering effect is shown in Table 1.

[0057] Comparative Example 1

[0058] The difference from Example 1 is that only silica sol solution is used to replace the nano-dispersion liquid in Example 1. The specific filtering effect is shown in Table 1.

[0059] Comparative Example 2

[0060] The difference from Example 1 is that the glass particles are not treated in any way. The specific filtering effect is shown in Table 1.

[0061] Table 1 Comparison of glass filter material formulations and filtration effects of Examples 1-5 and Comparative Examples 1-2

[0062]

[0063]

[0064] As can be seen from Table 1, the glass filter materials prepared in Examples 1-5 use a dispersion containing nano-sized silicon oxide, zinc oxide, titanium oxide, aluminum oxide, and silica sol, which is sprayed on the surface of the glass particles and then dried and sintered to form a rough surface with a complex structure on the surface of the glass particles. The filter materials have high filtration accuracy and very low shading rate, especially Examples 1 and 4, where the filtration accuracy reaches below 1 μm.

[0065] Comparative Example 1 uses only silica sol solution. Since the silica particles are small and concentrated in size, they cannot provide a rough surface structure, and the material has limited dirt holding capacity and cannot improve the filtration accuracy. The shading rate is high. Comparative Example 5 does not undergo any treatment on the glass particles, so the filtration accuracy is similar to that of ordinary quartz sand, and the shading rate is also high.

[0066] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention is described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions recorded in the above embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. In addition, those skilled in the art can understand that although some embodiments herein include certain features included in other embodiments instead of other features, the combination of features of different embodiments means being within the scope of the present invention and forming different embodiments. For example, in the above claims, any one of the embodiments claimed for protection can be used in any combination. The information disclosed in this background technology section is only intended to deepen the understanding of the overall background technology of the present invention, and should not be regarded as admitting or suggesting in any form that the information constitutes prior art known to those skilled in the art.

Claims

1. A method for preparing a glass filter material, characterized in that: The nano-dispersed liquid is sprayed on the surface of glass particles, followed by drying and sintering to obtain the product.

2. The preparation method according to claim 1, characterized in that: The glass particles have a particle size of 0.1-4.0 mm.

3. The preparation method according to claim 1, characterized in that: The glass particles are subjected to surface cleaning treatment; The surface cleaning treatment includes plasma cleaning or ultraviolet irradiation; The plasma cleaning time is 1-10 seconds.

4. The preparation method according to claim 1, characterized in that: The preparation method of the nano-dispersion liquid comprises: preparing an aqueous solution of fumed silica, aluminum oxide, zinc oxide, titanium oxide and water according to weight parts, grinding, fully dispersing, then adding silica sol and water, stirring, and preparing a nano-dispersion liquid with a silica sol concentration of 5-35%.

5. The preparation method according to claim 4, characterized in that: The D50 of the fumed silica is 20-100 nm, and the BET specific surface area is 115-135 m 2 / g; The particle size of the aluminum oxide is 100-2000 nm, and the BET specific surface area is 5-10 m 2 / g; The particle size of the zinc oxide is less than 100 nm; The titanium oxide includes two crystal structures, rutile type and anatase type, and its particle size is less than 50nm.

6. The preparation method according to claim 4 or 5, characterized in that: In terms of parts by weight, the fumed silica, aluminum oxide, zinc oxide, titanium oxide and water are 1-50 parts, 1-10 parts, 0.1-20 parts, 0.1-20 parts and 100-800 parts respectively.

7. The preparation method according to claim 4, characterized in that: The ratio of the glass particles to the nano-dispersion liquid is 8-12 g / ml.

8. The preparation method according to claim 1, characterized in that: The drying temperature is 80-250° C., and the drying time is 5-60 min.

9. The preparation method according to claim 1, characterized in that: The sintering temperature is 500-700° C., and the sintering time is 5-30 min.

10. A glass filter material, characterized in that: The product obtained by the preparation method according to any one of claims 1 to 9 is screened into four grades, namely 0.1-0.4 mm, 0.4-0.8 mm, 0.8-2.0 mm and 2.0-4.0 mm, to adapt to different filtering accuracies.

Citation Information

Patent Citations

  • Preparation method of novel glass slag filter material with negatively charged modified surface

    CN110548339A

  • Titaniferous composition, method for forming nano particle film on ceramic or glass surface from titaniferous composition and application of titaniferous composition

    CN102464499A

  • Finishing method of filter material with functions of water resistance and static resistance

    CN104631093A

  • Waterborne glass nano-paint containing composite metal nanometer nuclear particles and preparation

    CN108250928A

  • Inorganic composite diaphragm and preparation method thereof

    CN109728231A